Analysis of the Development of Electric Car Marketing in Indonesia in Encouraging Consumer Purchasing Interest - Garneta Dinarsuci; Yulianah Yulianah; Mohammad Nabilulhaq Diforama; Putri Pratiwi; Shahnawaaz Kiara Amanda; R. Dewi Pertiwi (Advances: Jurnal Ekonomi & Bisnis, 2026)
Purpose: This study analyzes the development of electric-car marketing strategies in Indonesia and examines how green marketing, government incentives, infrastructure readiness, and consumer behavioral factors influence purchase intention for electric vehicles. Research Method: This study employed a qualitative descriptive approach using literature review and document analysis. Data were collected from GAIKINDO reports, Scopus- and SINTA-indexed journals, government regulations, business publications, and observations of digital marketing campaigns from 2022 to 2025. Data were analyzed using thematic coding, data reduction, and triangulation. Results and Discussion: The findings indicate that consumer purchase intention is influenced by economic efficiency, technological innovation, environmental awareness, social influence, and perceived behavioral control. Government incentives, charging infrastructure expansion, battery warranty schemes, and omnichannel marketing strategies contributed to increasing consumer confidence and market acceptance of electric vehicles. Implications: The study highlights the importance of integrating green marketing communication, ecosystem readiness, and infrastructure support to strengthen sustainable electric vehicle adoption in Indonesia. Originality: This study integrates green marketing and the Theory of Planned Behavior to explain electric vehicle purchase intention in the Indonesian market.